Survey on the Intermediate Hosts of the Layer Parasites in an Open-Farm System in Na Bon District, Nakhon Si Thammarat Province - Uttayarak, Pornpitcha; Leelasakulmeekead, Wetaka; Jarujareet, Wipaporn; Thanasut, Khompakorn (Recent Science and Technology, 2024)
Gastrointestinal parasites are a major cause of economic impact on the layers because they will reduce productivity. Some helminths need an intermediate host for multiplication or carriers to be able to complete their life cycle. The objective of this study was to investigate what type of insects could be the intermediate host of parasites in layers. Insects were collected from an open-farm system laying hen farm in Nabon District, Nakhon Si Thammarat Province between December 2020 and January 2021. One hundred insect samples were subjected to dissect and examine parasites in the digestive tract under a light microscope. The result revealed that the intermediate host of Oxyspirura spp. was the cockroach (Pycnoscelus surinamensis) at 8.70% prevalence in adult and 9.52% prevalence in nymph (2/23 samples and 2/21 samples) and the darkling beetle (Alphitobius diaperinus) at 15.39% prevalence (8/52 samples). Moreover, both species would also be accidentally infected by nymph of mites. Therefore, besides focusing on the cockroach and the darkling beetle, farmers must concentrate on mite removal.